THE INCIDENCE OF IN-HOSPITAL MALNUTRITION IN CHILDREN AT SANGLAH DENPASAR HOSPITAL - Lanang Sidiartha, I Gusti (Medicina; Vol 43 No 1 (2012): Januari 2012)
In-Hospital Malnutrition cause by longer length of stay is still as a health problem. The objective of the study is to find out the incidence of In-hospital malnutrition and the association with sex, age, malnutrition on admission, diagnosis and length of stay. The cohort retrospective study was done based on the medical record from The Nutrition and Metabolic Disease Division, Department of Child Health, Udayana University/Sanglah Hospital Denpasar from June 2008 to February 2009 period. In-hospital malnutrition was confirmed if the body weight decreased ? 2% in a week or ? 5% in a month or ? 10% in 6 months during hospitalized. Statistical analysis was done to find out the association between In-hospital malnutrition and sex, age, diagnosis, malnutrition on admission, and length of  stay. The odds ratio was counted and the statistical significant was decided if p value < 0.05. There were 78 over 460 children (17%) met the criteria of In-hospital malnutrition. Logistic regression showed that after adjusting for sex, age, malnutrition on admission, and diagnosis; the length of stay longer than 7 days (OR = 3.7, CI 95% 2.1 – 6.4) was statistically associated with In-hospital malnutrition in the final model. The study concludes that the incidence of In-hospital malnutrition in Sanglah Hospital was still high and it was associate with length of stay longer than 7 days. (MEDICINA 2012;43:15-18).
Keywords: malnutrition, weight loss